Comparative Analysis of The Development of Chinese Language Teaching in Indonesia and Malaysia——Focusing on Bereday's Four Step Method of Comparative Education Research: 印尼的中文教学发展与马来西亚对比分析——以贝雷迪的比较教育研究四步法为主 - David Vincensius (Published by Confucius Institute UNS, 2024)
At present, Chinese teaching as a second language is becoming more and more famous, especially in countries along the One Belt One Road. As part of the One Belt One Road, Indonesia and Malaysia are no exception. Indonesia and Malaysia are neighboring countries in Southeast Asia. The purpose of this study is to compare educational research, using Bereday's